Characterization of ampicillin resistance mechanisms in clinical Haemophilus influenzae strains isolated in Portugal between 2009 and 2012 - Guilherme, Elsa (2016)
Introduction: Haemophilus influenzae (Hi) is mainly responsible for respiratory infections and empirical therapy is used most of times. Ampicillin resistance is a problem of concern since some strains have diminished susceptibility to β-lactams through a non-enzymatic mechanism that involves decreased affinity of β-lactams for altered penicillin-binding proteins (PBPs). Strains exhibiting this resistance mechanism are referred as β-lactamase-negative ampicillin resistant (BLNAR). The aim of this study is to characterize ampicillin resistance mechanisms in clinical isolates of Hi in Portugal. Material and Methods: Two hundred and thirty-five isolates chosen according to their ampicillin MICs: 139 BLNAR (MIC≥1mg/L), 33 susceptible strains (BLNAS; MIC<1mg/L) and 63 β-lactamase producers (BLPAR) were analyzed. The ftsI gene encoding PBP3 was amplified and sequenced. MIC was determined for 13 antibiotics by a microdilution assay, according to CLSI guidelines. Results and Discussion: Of the 235 Hi isolates 199 had mutations in the ftsI transpeptidase domain as follow: 136 gBLNAR out of 139 BLNAR strains (98%) and 44 gBLPACR out of 63 BPLAR strains (70%). Of note, 19 out of 33 BLNAS (58%) presented mutations being designated as gBLNAR. Among gBLNAR and gBLPACR strains there were 43 different mutation patterns, that were included in the six previously described groups and subgroups (I, IIa, IIb, IIc, IId, III-like). The most common amino acid substitutions were located near KTG motif: N526K (160/199, 80.4%), V547I (140/199, 70.4%) and N569S (131/199, 65.8%). Strains with mutations were less susceptible to the β-lactam antibiotics studied. Comparing these results with previously ones, performed in our laboratory (between 2001 and 2008) we are assisting to an increase of susceptible strains (ampicillin MIC≤2mg/L) as well as resistant strains (beta-lactamase producers) with mutations in the ftsI gene, being so called gBLNAR and gBLPACR. CLSI breakpoints alone can’t characterize these strains as susceptible or resistant in the susceptibility tests performed routinely in the laboratory. In this way, a continuous research on breakpoints and methodologies to better define strains of this kind is of crucial importance. In conclusion, we emphasize the importance of continuing surveillance studies of this nature as essential tools to define trends in the antibiotic resistance of Hi.